2006
DOI: 10.1002/wcm.295
|View full text |Cite
|
Sign up to set email alerts
|

On efficacy of Rayleigh‐inverse Gaussian distribution over K‐distribution for wireless fading channels

Abstract: For studying performance characteristics of radio channels, the knowledge about the probability density function (pdf) of fading–shadowing effects is essential. K‐distribution corresponding to Rayleigh–gamma distribution (RGD) is widely used to approximate a more realistic Rayleigh–lognormal distribution (RLD) which does not have a closed form expression. A new composite Rayleigh‐inverse Gaussian distribution (RIGD), an alternative to K‐distribution, is analyzed with regards to its suitability and effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 10 publications
0
64
0
Order By: Relevance
“…In this regard and by using the same approach as presented in [17], it was shown that the Nakagami-Inverse lognormal distribution has a closed form given by [20, Equation (5)]:…”
Section: Gg-l Composite Model With V = 1 (N-l)mentioning
confidence: 99%
“…In this regard and by using the same approach as presented in [17], it was shown that the Nakagami-Inverse lognormal distribution has a closed form given by [20, Equation (5)]:…”
Section: Gg-l Composite Model With V = 1 (N-l)mentioning
confidence: 99%
“…To the best of our knowledge, there exists no closed-form expression for the average probability of detection when we substitute (8) and (10) into (9). The log-normal distribution can be closely approximated by the Wald distribution (also known as the inverse Gaussian distribution) [11], [12], whose PDF is given by…”
Section: Local Energy Detection In a Slow Fading Channelmentioning
confidence: 99%
“…Following this, in many works focused on databit level analyses, gamma mixture distribution is utilized to characterize the shadow fading in composite models which include macroscopic and microscopic fadings together [8], [9]. Various other shadow fading models such as inverse Gaussian have also been considered in such composite channels [10].…”
Section: Introductionmentioning
confidence: 99%